Teacher S Digital Competence Among Final Year Pedagogy Students in Chile and Uruguay - Silva-Quiroz, J (Grupo Comunicar Ediciones, 2019)
The development of Teacher s Digital Competence (TDC) should start in initial teacher training, and continue throughout the following years of practice. All this with the purpose of using Digital Technologies (DT) to improve teaching and professional development. This paper presents a study focused on the diagnosis of TDC among ITT senior students from Chile and Uruguay. A quantitative methodology, with a representative sample of 568 students (N=273 from Chile and N=295 from Uruguay) was designed and implemented. TDC was also studied and discussed in relation to gender and educational level. Results showed a mostly basic level for the four dimensions of the TDC in the sample. Regarding the relationship between the variables and the TDC, the planning, organization and management of spaces and technological resources dimension is the only one showing significant differences. In particular, male students achieved a higher TDC level compared with female students. Furthermore, the proportion of Primary Education students with a low TDC level was significantly higher than other students. In conclusion, it is necessary, for teacher training institutions in Chile and Uruguay, to implement policies at different moments and in different areas of the ITT process in order to improve the development of the TDC. © ISSN: 1134-3478.